The Structures and Possible Sources of Preservice Elementary Teachers' Mental Models About Moon Phases - Jun-Young Oh; Yong-Hee Kang; Kye-Hwa Yoo (Journal of Astronomy and Space Sciences, 2005)
This study was to understand the components that influence preservice elementary teachers' mental models about `astronomical phenomena' such as the Seasons of the year, and the Lunar Phases of the month. We selected university of education students among whom 23 were in the second year. The data collected from the paper-pencil test and individual interview with students. The results of this study show that the students had apparent synthetic Mental models, and that the 'distance theory, and occultation theory' had most important effects on their Mental Models. It can be said that preservice elementary teachers' initial mental models of the `astronomical phenomenon' have their origin in their belief sets (specific theory) related to `astronomical phenomenon', on the basis of which they can interpret their observations and cultural information with the constraints of a naive framework of physics. The structures and possible sources of their mental models for overcoming these synthetic mental models were also discussed.